POVERTY LEVEL OF TOBACCO PRODUCER HOUSEHOLDS IN EASTERN JAVA PROVINCE (CASE STUDY OF TOBACCO FARMERS IN SITUBONDO REGENCY) - Atasa, Dita; Laily, Dona Wahyuning; Roidah, Ida Syamsu; Rizkiyah, Noor; Rozchi, Fatchur (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
In this study using Farmer Income Survey (SPP) data, in the 2022 agricultural research survey, it was proposed to identify the impact of individuals on poverty levels in tobacco farming households in Situbondo Regency. The data sample used is 200 farmers who work in the agricultural sector of tobacco farming. Based on the results of descriptive analysis, it was concluded that the category of the age group was less than 25 years, with a minimum of elementary school education, the number of household members less than 4 people and the head of the household the number of poor people was higher in farmers who were more than 25 years old, had elementary school education, had more of 4 household members, and has a female head of household. Households (KRT) who are female have a greater number of poor groups than those who are not poor. Based on binary logistic regression analysis showed that age, education, number of household members, employment status, and gender of the head of the household had a statistically significant effect on the poverty status of tobacco farmers in the tobacco farming sector in Situbondo Regency. Farmers in tobacco farming who are between 45 and 64 years old, well educated, have few household members, are self-employed and have a male head of household tend to be less poor.